2019
DOI: 10.1002/advs.201802297
|View full text |Cite
|
Sign up to set email alerts
|

Thermally Stable Donor–Acceptor Type (Alkynyl)Gold(III) TADF Emitters Achieved EQEs and Luminance of up to 23.4% and 70 300 cd m−2 in Vacuum‐Deposited OLEDs

Abstract: Thermally stable, strongly luminescent gold‐TADF emitters are the clue to realize practical applications of gold metal in next generation display and lighting technology, a scarce example of which is herein described. A series of donor–acceptor type cyclometalated gold(III) alkynyl complexes with some of them displaying highly efficient thermally activated delayed fluorescence (TADF) with Φ up to 88% in thin films and emission lifetimes of ≈1–2 µs at room temperature are developed. The emission color of these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
78
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

3
3

Authors

Journals

citations
Cited by 65 publications
(81 citation statements)
references
References 42 publications
3
78
0
Order By: Relevance
“…Complexes 4 , 7 and 8 , on the other hand, being short‐lived ( τ <2 μs) with large k r (ca. 10 5 –10 6 s −1 ) display emission behaviors that are similar to the reported Au III ‐TADF complexes . Thus, the emission of 4 , 7 , and 8 likely involves TADF.…”
Section: Resultssupporting
confidence: 74%
See 4 more Smart Citations
“…Complexes 4 , 7 and 8 , on the other hand, being short‐lived ( τ <2 μs) with large k r (ca. 10 5 –10 6 s −1 ) display emission behaviors that are similar to the reported Au III ‐TADF complexes . Thus, the emission of 4 , 7 , and 8 likely involves TADF.…”
Section: Resultssupporting
confidence: 74%
“…On the other hand, the radiative decay rate constants of phosphorescent Au III complexes are usually small as the emissive excited states, being mainly ligand localized, involve only minor metal parentage, which is detrimental in OLED applications because of large efficiency roll‐off . In this regard, OLEDs fabricated with Au I and Au III ‐TADF emitters ( τ <2 μs) have achieved small roll‐off (<10 %) . A recent study suggested that improving the rigidity of emitters could suppress the structural deformation upon S 1 –T 1 transformation thereby reducing the activation energy barrier for reverse intersystem crossing (RISC) and leading to efficient TADF .…”
Section: Introductionsupporting
confidence: 52%
See 3 more Smart Citations